Training load metrics and responses of flatwater, ocean and river marathon kayakers in preparation for competition - Notten, Nicholas (Department of Human Biology, 2026)
Background: Regular training improves performance, particularly in activities like marathon kayaking, which require conditioning for both explosive bursts and sustained endurance efforts. Monitoring training load ensures a balance of physiological stress and recovery, which is critical for optimised improvement. However, there are currently no evidence-informed standards for monitoring training load in marathon kayaking. Aims & objectives: The aim is to identify the training load measures and metrics relevant to ocean, flatwater, and river marathon kayaking. This involves exploring low-cost, non-invasive monitoring methods and addressing existing gaps in our understanding of monitoring training load in marathon kayaking. The focus is on determining the effectiveness of these metrics in guiding physical conditioning and overall training performance. Ultimately, the goal is to contribute to the development of monitoring methods that are effective and tailored to the specific context. Methods: This dissertation had three parts: a systematic scoping review of the literature to identify the extent of the evidence around monitoring practices in marathon kayaking, followed by a more focused narrative review to more precisely highlight the specific demands of marathon kayaking and establish broad areas of importance. Using insights from the scoping and narrative reviews as a framework, a longitudinal repeated measures observational study was conducted with a cohort of marathon kayakers (n=38). The investigation used various low-cost, non-aversive, remotely deployable tools to monitor the kayakers' training for eight weeks before a race. Primary findings: Rating of perceived exertion (RPE) was the most sensitive measurement of session intensity. Furthermore, session RPE was considered the most reliable measure of overall training because it is RPE-derived and aligned with other training accumulation measures. Speed and heart rate were useful metrics with context, such as environmental conditions or when used as relative measures. Training stress can be examined by psychometric measures (DALDA and quick POMS). This cohort had relatively low levels of training stress, which had a minimal effect on the psychometric measures. Time trials are an effective performance measure where course environmental impacts can be mitigated. Conclusions: At present, there are practical, non-aversive metrics that provide valuable insights into various aspects of kayak training, including total volume, intensity, response, and performance evaluation. When used in the correct context, these metrics can be effective and well-suited to the needs of competitive kayakers.